Lactobacillus gasseri APC 678 Reduces Shedding of the Pathogen Clostridium difficile in a Murine Model - Quigley, Lisa; Coakley, Mairéad; Alemayehu, Debebe; Rea, Mary C.; Casey, Patrick G.; O’Sullivan, Órla; Murphy, Eileen; Kiely, Barry; Cotter, Paul D.; Hill, Colin; Ross, R. Paul (Frontiers in Microbiology, 2019)
Clostridium difficile is a common cause of health-care acquired diarrhoea, resulting in a spectrum of disease from mild diarrhoea to life-threatening illness. Sixty Lactobacillus strains were screened for anti-C. difficile activity using a co-culture method. Based on their ability to inhibit C. difficile, L. gasseri APC 678 (PB-678TM) and L. rhamnosus DPC 6111 were selected for study in a murine model of C. difficile infection. L. gasseri ATCC 33323, was included as a control. It was established that, relative to control mice not fed Lactobacillus, feeding with L. gasseri APC 678 resulted in a significant reduction by day 7 (8-fold, p=0.017) of viable C. difficile VPI 10463 in the feces of mice. In contrast, neither L. rhamnosus DPC 6111 nor L. gasseri ATCC 33323 significantly reduced fecal C. difficile shedding. Sequencing of the cecal microbiota showed that in mice fed L. gasseri APC 678 there was a significant increase in bacterial diversity across a number of indices when compared to the control or other Lactobacillus-fed groups. There was no significant change in the relative abundance of Firmicutes or Bacteroidetes in the group fed L. gasseri APC 678 relative to the control, while the groups fed L. rhamnosus DPC 6111 or L. gasseri ATCC 33323 showed a significant decrease in the relative abundance of Firmicutes (p=0.002 and p=0.019, respectively) and a significant increase in Bacteroidetes (p=0.002 and p=0.023, respectively). These results highlight the potential of L. gasseri APC 678 as a live therapeutic agent to target C. difficile infection.